Editorial Letter" HIV-related Stigma: A Dilemma in the Prevention of HIV Spread - M Gharacheh; F Ranjbar (Iran University of Medical Sciences, 2018)
HIV/AIDS is a global health concern that spans three decades of its emergence(1). However, it remains a complex, unique issue among experts. While HIV/AIDS is medically recognized as a chronic, fatal disease, there is a social stigma attached to the disease, which targets the dignity of the patients. In addition to the burden of the disease, stress, and fear of death, an HIV-infected patient is faced with negative emotions, such as social rejection, prejudice, humiliation, and discrimination, so that HIV-related stigma seems to be more burdensome for the patients than the disease(2). Since HIV infection is associated with avoidable behaviors (e.g., unsafe sexual relations and substance abuse), the patients are often responsible for their own illness(3). On the same note, the failure of the media to properly inform people has led the populace to regard AIDS immoral(4). The fear of judgment or discrimination from others deeply affects the self-image of the patients with HIV infection, as well as their coping abilities. This experience may cause self-blame in the patients, who may, as a result, presume themselves to be deserving of maltreatment(5). They may even give up their rights to treat and receive other social benefits, which is associated with devastating effects on HIV prevention, care, and treatment. HIV-related stigma also interacts with cultural prejudices and gender issues. Globally, when a woman is infected with HIV, her status subjects her to more discriminatory treatment compared to a man. Therefore, many women living with HIV tend to hide their status from their spouses due to the fear of rejection, violence, and even death. This leads to the loss of the opportunity to prevent the infection of the spouse, and also deprives women of access to the necessary care and treatment(6). There is a cyclical relationship between stigma and HIV; the individuals who experience stigma and discrimination due to HIV infection are marginalized, thereby becoming more vulnerable to HIV. On the other hand, patients with HIV are more prone to discrimination and stigma than others(7). The World Health Organization has identified the fear of stigma and discrimination as the main barriers to HIV testing, HIV status disclosure, and access to HIV treatment. It is reported that in 35% of countries, more than 50% of the population have discriminatory attitudes toward HIV patients(8), and about one out of eight peopleinfected with HIV does not use health services due to the fear of discrimination and social stigma. In 2016, 60% of the countries across the world reported the discriminatory attitude of healthcare providers toward intravenous drug users, which in turn discourages them to provide adequate services for HIV prevention to these patients(9). HIV-related stigma and discrimination have been frequently observed in healthcare professionals at all levels, and the attitudes are manifested in a variety of manners. Healthcare providers may minimize their contact with HIV, neglect their proper care, delay their treatment, and isolate these individuals from other patients. However, the unwillingness of people to receive HIV testing delays the diagnosis of the disease, leading to its progression to the stage of AIDS and ineffective treatment, thereby increasing the risk of infection transmission and untimely death(7). Despite the advancement in the detection of HIV and its transmission, there have not been sufficient effort to reduce the social stigma and labeling attached to this disease(10,11). Management of HIV-related stigma and discrimination is a major impediment to the coordinated action at global, regional, national, and social levels, as well as a human rights obligation. Implementing specific programs that emphasize on the rights of HIV patients is a well-known way of eradicating HIV-related stigma(12). Stigma is a social construction(2), and it is imperative to adopt a comprehensive approach to deal with it. Therefore, tackling with stigma should be taken into consideration at the individual, social, organizational, and policy-making levels. At the individual level, raising public awareness regarding HIV transmission, care, and prevention, while ensuring access to proper services and legal rights is absolutely essential. Another influential factor in this regard is providing social support to HIV patients. In the educational programs for healthcare providers, the cultural stimuli for the establishment of HIV-related stigma and discrimination (e.g., fear of infection, prejudice toward vulnerable groups, and misconceptions/lack of knowledge regarding HIV transmission, treatment, and prevention) should be considered. Furthermore, the media should raise public awareness regarding HIV and its effects on the lives of people, thereby tackling HIV-related stigma through changing the false attitudes and emphasizing on the fact that patients with HIV have the same human rights as others. At the policy-making level, factors such as discrimination in employment, education level, health service provision, and other needs of HIV patients must be addressed. Eradicating the discrimination and stigma attached to HIV infection, which is a major obstacle to access to health and preventive services, is the key to stopping the HIV epidemic.